Fast and efficient identification of hyaluronidase specific inhibitors from Chrysanthemum morifolium Ramat. using UF-LC-MS technique and their anti-inflammation effect in macrophages. Issue 2 (February 2023) - Zhou, Huiji; Zhang, Xue; Li, Bo; Yue, Rongcai
Abstract: The purpose of the study was to establish a rapid analytical strategy to screen potential anti-inflammatory compounds from Flos Chrysanthemum flower. The enzyme assay was conducted to prescreen botanical extracts, in which Chrysanthemum morifolium aqueous extract (CME) displayed hyaluronidase (HAase) inhibitory activity in a dose-dependent manner with the values of 8.31, 24.25, and 66.51% at concentrations of 1.00, 2.00, and 4 0.00 mg/mL, respectively. Eight potential compounds targeting HAase (compounds 9, 10, 11, 13, 15, 17, 20 and 21 ) from CME were screened using ultrafiltration affinity liquid chromatography coupled with mass spectrometry (UF-LC-MS) technology. The well-known inhibitor, dipotassium glycyrrhizinate (DG), was used as a positive control and competitive ligand to eliminate false positives. Then, four of these potential components (compounds 9, 10, 17, and 21 ), namely eriodictyol-7- O -glucoside, luteoloside, apigenin-7- O -glucoside and diosmetin-7- O -glucoside, were distinguished as potent HAase specific inhibitor candidates with high BD and CBD values. The enzyme inhibitory activities of candidate compounds were verified using enzyme inhibition assay. At a concentration of 1000 μM, compounds 9, 10, 17, and 21 showed 40.15, 44.85, 18.04, and 24.15% inhibition of HAase, respectively. Furthermore, all the four compounds significantly decreased the production of nitric oxide (NO) and IL-6, and significantly suppressed the mRNA expression of inducible NO synthase (iNOS) and IL-1β in both murine and human macrophages.